HUBUNGAN PENGETAHUAN DENGAN KEPATUHAN DIET PADA PASIEN DIABETES MELITUS TIPE II - Wiwin A Muhammad; Nelfa Fitria Takahepis; Nurlela Hi Baco (Jurnal Rumpun Ilmu Kesehatan, 2022)
Diabetes Mellitus (DM) is a chronic disease that occurs when the pancreas is disable to produce insulin, which isenergy. Good knowledge determines adherence to diet in patients with type 2 diabetes mellitus. The purpose of this study was to determine the relationship between knowledge and dietary compliance of patients with type II diabetes mellitus at WolterMonginsidiTk.IIHospital Manado. This study was conducted in August on patients with diabetes mellitus at WolterMonginsidiTk.IIHospital Manado with population are 141 respondents and 35 respondents was taken as samples of this research with using non-probability sampling technique type which is accidental sampling technique. The type of this research was using descriptive analytic method with a cross sectional approach, and used questionnaire as research instrument. The data was collected and analysed using Chi-square test with a significance (α) ≤0.01. The results of Chi-square statistical test obtained ρ-value (α = 0.01). This means that there is a significant relationship between knowledge and dietary compliance in patients with diabetes mellitus at the WolterMonginsidiTk.II Hospital Manado. The conclusion of this studythere is a relationship between knowledge and dietary compliance in patients with diabetes mellitus. The suggestion from this study is hopefully this study can give benefit in Nursing development.